Breaking the Recycling Bottleneck of Thermosets via Bio‐Tailoring Technology - Jinping Yu; Huan Wang; Yang Xu; Boutrous Wemegah; Yang Lan; Jing Li; Li Yang; Guanjun Chang (Advanced Science, 2025)
Abstract Thermosets present significant recycling challenges due to irreversible chemical crosslinking, resulting in resource waste and environmental pollution. This paper introduces a new strategy for designing thermosets with excellent recycling properties driven by Bio‐Tailoring technology, achieving amazing green sustainable development. These thermosets are a class of infusible and insoluble polymers owing to chemical crosslinking. The indole groups in the cross‐linked network can be accurately identified and tailored by microorganisms, giving rise to the cross‐linked network being tailored into new linear polymers and small molecule segments, named the Bio‐Tailoring technology. Linear polymers can be used as a new plastic packaging material that involves high transparency and appreciable mechanical properties. Meanwhile, the cross‐linked small molecule moiety is a fluorescent functional unit with a unique push‐pull electronic structure that leads to color‐changing under external stimulation and can be applied to anti‐counterfeiting. Overall, this strategy provides an innovative solution for the sustainable recycling of thermosets and opens a new path for the environmental transformation of the plastics industry.